Two Models of Integrating Buprenorphine Treatment and Medical Staff within Formerly "Drug-Free" Outpatient Programs. Issue 2 (14th March 2016) - Monico, Laura; Schwartz, Robert P.; Gryczynski, Jan; O'Grady, Kevin E.; Mitchell, Shannon Gwin
ABSTRACT: "Drug-free" outpatient programs deliver treatment to the largest number of patients of all treatment modalities in the U.S., providing a significant opportunity to expand access to medication treatments for substance use disorders. This analysis examined staff perceptions of organizational dynamics associated with the delivery of buprenorphine maintenance within three formerly "drug-free" outpatient treatment programs. Semi-structured interviews (N = 15) were conducted with counseling and medical staff, and respondents were predominantly African American (n = 11) and female (n = 12). Themes and concepts related to medical staff integration emerged through an inductive and iterative coding process using Atlas.ti qualitative analysis software. Two treatment clinics incorporated buprenorphine maintenance into their programs using a co-located model of care. Their staff generally reported greater intra-organizational discord regarding the best ways to combine medication and counseling compared to the clinic using an integrated model of care. Co-located program staff reported less communication between medical and clinical staff, which contributed to some uncertainty about proper dosing and concerns about the potential for medication diversion. Clinics that shift from "drug-free" to incorporating buprenorphine maintenance should consider which model of care they wish to adapt and how to train staff and structure staff communication.